Perancangan Interior Supermarket Golden Sweet di Kendari, Sulawesi Tenggara - Dodi Wondo, Fenny Widjaja Mariana Wibowo (Intra, 2013)
Supermarket is currently experiencing rapid growth, it can even be becoming a trend setter / icon in a city, as well as the city of Kendari, Southeast Sulawesi. But along with the development of the supermarket also growing more and more, even in one city, there can be a supermarket. With so many existing supermarkets will be required one / supermarket that is different from the others to be the icon of the city. In addition to icon, supermarkets should also be able to be a facilitator for the community to meet their needs, not just as a place to purchase the product. So that people who come to the supermarket can be satisfied with the facilities and feel of space inside. By applying its unique design and element of local culture, in addition to meeting basic needs - today, the supermarket with the concept of All in One Market, is expected to design a supermarket in the town of Kendari can be a trend setter / icon Kendari city that does not leave the typical culture of the city of Kendari. With the data - the data and understanding of the culture of Kendari, the All in One Market design can be done properly, which can lead to the design of unique design and become an icon Kendari city.